The Generating Indonesian Paraphrased Sentences with Verbal Predicate Replacement - Bunyamin; Suryani, Arie Ardiyanti (Indonesian Journal on Computing (Indo-JC), 2023)
Sentence paraphrasing is restating sentences using different diction without changing the meaning of the language. Paraphrasing sentences can be done in several ways, including synonym substitution techniques, changing sentence forms, or replacing the predicate part of sentence. This research aims to produce a paraphrased sentence generator with semantic similarities to the original sentence. The paraphrasing used in this research is to identify the verb type predicate in simple sentences using PoS Tagging. Then look for words similar to the predicate using the similarity of the word2vec model. A list of opposites antonyms is used to improve the lexical substitution results. Evaluation is done by using human judgment between the results and the original sentence. The experimental results show that of the 600 sentence datasets, 48.37% of the sentences have semantic similarities, 20.93% have semantic reductions, and 30.70% have no semantic similarities.